Water ADC, extracellular space volume, and tortuosity in the rat cortex after traumatic injury - Vorísek, I; Hájek, M; Tintera, J; Nicolay, K; Syková, E (Magnetic resonance in medicine, 2002)
The diffusion parameters in rat cortex were studied 3-35 days following a cortical stab wound, using diffusion-weighted MR to determine the apparent diffusion coefficient of water (ADC(W)) in the tissue, and the real-time iontophoretic tetramethylammonium (TMA) method to measure the extracellular space (ECS) diffusion parameters: ECS volume fraction alpha and the ADC of TMA(+) (ADC(TMA)). Severe astrogliosis was found close to the wound, and mild astrogliosis was found in the ipsilateral but not the contralateral cortex. Chondroitin sulfate proteoglycan (CSPG) expression was increased throughout the ipsilateral cortex. In the hemisphere contralateral to the wound, alpha, ADC(TMA), and ADC(W) were not significantly different from control values. ECS volume fraction was increased only in the vicinity of the wound, in the region of cell death and severe astrogliosis, at 3 and 7 days after injury. However, both ADC(TMA) and ADC(W) were significantly decreased after lesion in the vicinity of the wound as well as in the rest of the ipsilateral hemisphere distant from the wound. Thus, both ADC(W) and ADC(TMA) decreased in regions wherein alpha did not change but CSPG increased. An increase in extracellular matrix expression may therefore impose diffusion barriers for water as well as for TMA molecules.
Keywords: Magnetic Resonance Imaging; poranění mozku; magnetická rezonanční tomografie; senzitivita a specificita; Sensitivity and Specificity; mapování mozku; Ganglionic Stimulants; krysa rodu Rattus; magnetická rezonanční spektroskopie; zvířata; gangliová stimulancia; Immunohistochemistry; mozková kůra; imunohistochemie; potkani Wistar; Cerebral Cortex; Brain Mapping; difuze; Rats, Wistar; Diffusion; Male; voda; Extracellular Space; Rats; Water; Animals; Brain Injuries; Magnetic Resonance Spectroscopy; mužské pohlaví; glióza; Disease Models, Animal; Gliosis; modely nemocí na zvířatech; extracelulární prostor